Global liquidity and exchange rates - Tobias Adrian; Erkko Etula; Hyun Song Shin (Federal Reserve Bank of New York, 2009)
We present evidence that the funding liquidity aggregates of U.S. financial intermediaries forecast exchange rate growth-at weekly, monthly, and quarterly horizons, both in-sample and out-of-sample, and for a large set of currencies. We estimate prices of risk using a cross-sectional asset pricing approach and show that U.S. dollar funding liquidity forecasts exchange rates because of its association with time-varying risk premia. We provide a theoretical foundation for a funding liquidity channel in an intertemporal equilibrium pricing model where the 'risk appetite' of dollar-funded intermediaries fluctuates with the tightness of their balance sheet constraints. Our empirical evidence shows that this channel is separate from the more familiar 'carry trade' channel.
Keywords: F30; F31; G12; G24; 330; Asset pricing; financial intermediaries; exchange rates